Dendritic cells potently purge latent HIV-1 beyond TCR-stimulation, activating the PI3K-Akt-mTOR pathway - van Montfort, Thijs (EBioMedicine, 2019)
BACKGROUND: The latent HIV-1 reservoir in treated patients primarily consists of resting memory CD4(+) T cells. Stimulating the T-cell receptor (TCR), which facilitates transition of resting into effector T cells, is the most effective strategy to purge these latently infected cells. Here we supply evidence that TCR-stimulated effector T cells still frequently harbor latent HIV-1. METHODS: Primary HIV-1 infected cells were used in a latency assay with or without dendritic cells (DCs) and reversion of HIV-1 latency was determined, in the presence or absence of specific pathway inhibitors. FINDINGS: Renewed TCR-stimulation or subsequent activation with latency reversing agents (LRAs) did not overcome latency. However, interaction of infected effector cells with DCs triggered further activation of latent HIV-1. When compared to TCR-stimulation only, CD4(+) T cells from aviremic patients receiving TCR + DC-stimulation reversed latency more frequently. Such a “one-two punch” strategy seems ideal for purging the reservoir. We determined that DC contact activates the PI3K-Akt-mTOR pathway in CD4(+) T cells. INTERPRETATION: This insight could facilitate the development of a novel class of potent LRAs that purge latent HIV beyond levels reached by T-cell activation.